(untitled) (Jurnal Lemhannas RI, 2024)
Purpose: This study aims to explore the role of digital technology, particularly webinars, in enhancing national resilience by fostering civic engagement and strengthening national insight during the Covid-19 pandemic. Study Design/Methodology/Approach: A qualitative research methodology was employed to investigate how webinars serve as a platform for promoting national resilience through socialisation and practical education. The study focuses on the cognitive, affective, and psychomotor dimensions of online learning and civic participation across various demographics. Findings: The study finds that webinars, despite their virtual nature, successfully fulfil educational objectives, including promoting civic engagement and adaptability to technology. This shift from traditional education formats enables a broader reach, transcending the limitations of time and space, and contributes to building a resilient and cohesive society. The versatility of webinars offers organisers and participants an effective means of addressing diverse needs while promoting collective responsibility and social harmony. Originality/Value: This study highlights the innovative application of digital platforms like webinars as a vital tool in education and social engagement, emphasizing their role in strengthening national resilience and empowering citizens to address complex societal challenges. The findings contribute to the broader understanding of how virtual learning environments can effectively support civic education and social cohesion.